Chromium-Catalyzed, Regioselective Cross-Coupling of C–O Bonds by Using Organic Bromides as Reactants - Tang, Jinghua; Luo, Meiming; Zeng, Xiaoming (Synlett, 2017)
We report a chromium-catalyzed cross-coupling of C–O bonds with widely accessible organic bromides as reactants for the preparation of ortho-arylated or -alkylated aromatic aldehydes at room temperature. The use of metallic magnesium is essential for the reaction to occur, giving it an advantage over previous reactions involving Grignard reagents that have to be prepared separately from organic halides before the coupling.
Keywords: chromium; C–O activation; cross-coupling; C–C bond formation; organic bromides; regioselectivity